Media Literacy and Fake News: Bangladesh Perspective - Valerii L Muzykant; Barek Hossain; Munadhil abdul Muqsith; Mobassera Jahan Fatima (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Social media have become an integral element of modern life. Internet accessibility has boosted the public's engagement in computer-controlled official and informal activities. However, many information sources contain unsupported, inaccurate, and erroneous material. In this circumstance, media literacy is a significant phenomenon in developing and non-developing nations. Due to the misuse of social media and lack of media literacy in Bangladesh, some unexpected communal acts of violence happened during the past decade. This study intends to emphasize, from a Bangladeshi viewpoint, the significance of media literacy in reducing rumors, misinformation, disinformation, and fake news. Using descriptive research methodologies, more than forty secondary data sources from Bengali, English, Russian, Indonesian, and Turkish literature, such as research papers, reports, news stories, publications, books, and theses, have been examined. In order to combat misinformation, rumors, fake news, and yellow journalism in developing nations like Bangladesh, where literacy rates are still low, it is imperative to increase media literacy levels. In this regard, governments and non-governmental groups should work collaboratively to fix the deficiencies in this process.